Mathematics Learning Experiences of Students in Children Homes in Surkhet District, Nepal - Shahi, Mahendra Bahadur (Journal of Educational Research and Innovation, 2025)
This study explores the mathematics learning experiences of students living in children’s homes in the Surkhet district of Nepal. Using a qualitative approach, data were collected through interviews, focus group discussions and classroom observations with students, teachers, and caretakers. The findings show that most students see mathematics as a difficult and fearful subject, often feeling anxious and lacking confidence, which affects their motivation and performance. Many students also struggle with weak foundational skills because they were promoted to higher grades without fully understanding fundamental concepts. Limited personal guidance from teachers further adds their difficulties, as lessons often focus on completing the syllabus rather than addressing individual learning barriers. Peer group studies were found to be minimally effective due to lack of structure and proper study materials, while caretakers were unable to provide academic help because of heavy responsibilities, large numbers of children, and lack of training. Overall, the study reveals that students face emotional, academic, and environmental challenges that hinder their progress in mathematics. It highlights the need for stronger support systems, including personalized guidance, confidence-building activities, improved teaching practices, effective peer learning, and better collaboration between schools and children’s homes.